Development of Technological Learning Media to Increase Students' Civic Knowledge - M. Malik Purnama; M. Mona Adha; Ryzal Perdana; Dina Maulina (IJORER : International Journal of Recent Educational Research, 2024)
Objective: This study focused on developing Bekatal learning media (Digital Civics Education) to enhance students' civic knowledge. This was motivated by issues identified in students' understanding of civic knowledge. The study analyzed the feasibility and effectiveness of Bekatal learning media for enhancing students' civic knowledge. Method: The research employed the Four D (4D) model, involving samples from both experimental and control classes. Results: The findings indicate that the Bekatal learning media developed to enhance students' civic knowledge is feasible for use, with expert The findings show that the Bekatal learning media which was developed to increase students' civic knowledge is suitable for use, with the categories of very appropriate assessment from subject matter experts, very appropriate from media experts, very appropriate from language experts, and very appropriate from evaluation experts. Furthermore, from the results of the t-test, it can be concluded that there is an increase in students' civic knowledge before and after using Bekatal learning media. Based on these data, it can be concluded that the Bekatal learning media is feasible and effective in enhancing students' understanding of civic knowledge. Novelty: This research provides an innovative technological learning media that makes users feel the sensation of playing with learning materials by the learning objectives. So that users feel energized and like they are learning but feel like they are playing.